Does firm's silence drive media's attention away? - Sasan Mansouri (ZBW - Leibniz Information Centre for Economics, 2021)
In this study, using a comprehensive dataset on business media coverage and textual analysis of the discussions in firms' quarterly earnings conference calls, we show that firms whose management fail to satisfy the demand for information, ceteris paribus, receive less media coverage. Poor information environment hurts the information-creation capacity of the media, while such an environment does not show a similar association with the media's information-dissemination role. Furthermore, this association is more prominent for the professional business media, compared to their nonprofessional counterparts such as blogs and alternative articles. Our results add nuance to the literature on media coverage bias by showing that the coverage of the firms is mainly driven by the supply-side factors, i.e. the factors affecting the suppliers of the coverage, rather than being demand-driven.
Keywords: D82; G14; G30; 330; non-answers; conference calls; media coverage; non-professional business media